2011
DOI: 10.1111/j.1476-5381.2011.01514.x
|View full text |Cite
|
Sign up to set email alerts
|

Desmoteplase: discovery, insights and opportunities for ischaemic stroke

Abstract: Nature has provided a vast array of bioactive compounds that have been exploited for either diagnostic or therapeutic use. The field of thrombosis and haemostasis in particular has enjoyed much benefit from compounds derived from nature, notably from snakes and blood-feeding animals. Indeed, the likelihood that blood-feeding animals would harbour reagents with relevant pharmacology and with potential pharmaceutical benefit in haemostasis was not too far-fetched. Blood-feeding animals including leeches and tick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 96 publications
(128 reference statements)
0
47
0
1
Order By: Relevance
“…Actually, the only molecule that has been molecularly and functionally characterized so far in bat saliva is the plasminogen activator desmoteplase, which has been tested in clinical trials as a thrombolytic for the treatment of ischemic stroke. 21 More recently, the first comprehensive transcriptome analysis and proteome studies of D. rotundus submaxillary glands were reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the only molecule that has been molecularly and functionally characterized so far in bat saliva is the plasminogen activator desmoteplase, which has been tested in clinical trials as a thrombolytic for the treatment of ischemic stroke. 21 More recently, the first comprehensive transcriptome analysis and proteome studies of D. rotundus submaxillary glands were reported.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, prothrombinase was not inhibited when reactions were started with prothrombin/Desmolaris (not shown, n 5 4). It has been reported that Protein S enhances FXa inhibition by TFPI in the presence of phosphatidylcholine/phosphatidylserine/phosphatidylethanolamine and Ca 21 . 29,30 Although Protein S (0-160 nM) increases the inhibition of FXa (0.5 nM) by TFPI, no change was observed with Desmolaris (10 nM) (not shown).…”
mentioning
confidence: 99%
“…Still the gold standard therapy for acute ischemic stroke, 36 tPA is neurotoxic, 25 and the use of urokinase or desmoteplase avoids these complications inherent to tPA. 37,38 This has the potential to widen the currently very narrow therapeutic window for stroke thrombolysis of 3 to 4 hours. 6 The truncated, low-molecular-weight form scuPA is the preferred entity over full-length urokinase because it provides a smaller size with improved thrombus accessibility, no immunogenicity, and similar fibrinolytic potency.…”
Section: Discussionmentioning
confidence: 99%
“…Recently multicentre trial proved the safety and feasibility of tenecteplase in patient with minor strokes 26 . Fourth generation thrombolytic, desmoteplase is a highly fibrin-specific plasminogen thrombolytic agent, is the recombinant version of the plasminogen activator derived from the saliva of a vampire bat 27 . An in-vitro study show the variation with alteplase, desmoteplase does not increase blood brain barrier (BBB) permeability.…”
Section: Other Thrombolytic Agentsmentioning
confidence: 99%